CREATIVE ACCOUNTING AND THE GODFATHER STUDI KASUS PADA PT. GBU - Luky Amelia Chandra (CALYPTRA, 2017)
Abstract Purpose - This study aims to improve understanding of the creative accounting, so that it can detect the presence of creative accounting and how big the role of "The Godfather" or a special figure in providing influence to the culture of the organization so that it appears a practice creative accounting. Design / methodology / approach - Methodology used in the research begins with the collection of data from interviews, observation, and documentary analysis. Based on the dimensions of data sources, this research included in the field research. Findings - The result of this study is a special figure that has a very large role in shaping the culture of the organization so that it can occur creative accounting. Because the emergence of creative accounting in a company based on a certain destination, where the condition of the financial statements were not as expected, so do an act of creative accounting, then financial statements of these company can meet the expectations of the company. The organizational culture of a company affects the acts of creative accounting, where the organization members's background such as religion, education, age, gender, and occupation can influence the views and actions of the creative accounting. The role of "The Godfather" or a special figure in an organization in shaping the organizational culture is very strong, "The Godfather" can emphasize to his organization members that the act of creative accounting is a natural thing, because it has the objective to facilitate cash flow within the company and not with the intention of committing fraud so that creative accounting is deemed to be ethical. Keywords: Creative accounting, The Godfather, Special figure, Organizational culture.